SATB2 Is Expressed in a Subset of Pulmonary and Thymic Neuroendocrine Tumors. Issue 5 (12th May 2021) - Vrana, Julie A; Boland, Jennifer M; Terra, Simone B S P; Xie, Hao; Jenkins, Sarah M; Mansfield, Aaron S; Molina, Julian R; Cassivi, Stephen D; Roden, Anja C
Abstract: Objectives: To evaluate SATB2 expression and prognostic implications in a large cohort of thoracic neuroendocrine tumors. Methods: Surgical pathology files (1995-2017) and an institutional thymic epithelial tumor database (2010-2020) were searched for resected neuroendocrine tumors. Cases were stained with SATB2 (clone EP281). Percent SATB2-positive tumor cells and expression intensity were scored. Results: In the lung, SATB2 was expressed in 5% or more of tumor cells in 29 (74.4%) of 39 small cell carcinomas and 9 (22.5%) of 40 atypical and 26 (40.6%) of 64 typical carcinoid tumors. SATB2 percent tumor cell expression and intensity were higher in small cell carcinomas than in carcinoid tumors (both P  < .001, respectively). After adjusting for tumor subtype, SATB2 expression did not correlate with outcome. In the thymus, four (100%) of four atypical carcinoid tumors and one large cell neuroendocrine carcinoma but no small cell carcinoma (n = 2) expressed SATB2 in 5% or more of tumor cells. Conclusions: SATB2 (clone EP281) is expressed in a large subset of pulmonary and thymic neuroendocrine tumors and therefore does not appear to be a useful marker to identify the origin of neuroendocrine tumors. Validation studies are needed, specifically including thymic neuroendocrine tumors, as the expression pattern might be different in those tumors.